The Role of “Willfulness” in Creating Desperate Necessity (Iḍṭirār) and its Jurisprudential and Legal Consequences - Mohammad Reza hamidi (مطالعات تطبیقی فقه و اصول مذاهب)
In jurisprudence and criminal law, desperate necessity (iḍṭirār) is considered among the justified causes of a crime, according to which, the desperate person will not have any criminal liabilities for their actions. However, in cases where the “willfulness” (ta‘ammud) element can be considered involved in the emergence of the state of iḍṭirār, the exclusion of the criminal liability will not take place. The determination of the semantic range of iḍṭirār is a controversial issue among the criminal authorities. In the Holy Qur’an, this issue is touched upon in the five verses relating to iḍṭirār and interpreters and jurists have tried to resolve the semantic uncertainty of the words in these verses considering the relevant principles. The jurisprudential discourses in this context are strongly affected by the above-mentioned verses and they are in a way jurisprudential interpretation of verses of iḍṭirār. In this writing, using the analytical-descriptive method, while explaining the principles of the opinions jurists and interpreters, a solution is presented to resolve the ambiguity mentioned above. Hence, the conditions of iḍṭirār verses have semantics overlapping and the common value and agreed certitude of all of them should be considered as general condition for the verdict of dissolution of iḍṭirār. Therefore, only creating iḍṭirār with the intention of perpetrating an illicit action or by knowing its inevitability to commit it can be considered willfulness in creating iḍṭirār, and in these situations the criminal liability will remain true.